PENGGUNAAN CTL DENGAN MEDIA YOUTUBE UNTUK MEINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK KELAS XI MIPA 1 SEMESTER GENAP PADA MATERI INDIKATOR ASAM BASA DI SMA N 1 WEDI TAHUN PELAJARAN 2021/2022 - Theresia Gandes Kusumastuti Gandes (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
The CTL (Contextual Teaching and Learning) method is a learning model that provides facilities for students' learning activities to seek, manage, and find learning experiences that are more concrete and relate to real life. This method has the potential to increase understanding of the material because it is learning by doing and knowing its benefits in real life (contextual) and can encourage student creativity, namely through making videos and uploading them to YouTube. Research on the Use of CTL with Youtube Media on Acid-Base Indicator Material for Class XI MIPA 1 Even Semester SMA Negeri 1 Wedi Academic Year 2021/2022, aims to organize comfortable and happy learning. In this study, students were randomly divided into several groups. Each group looked for alternative materials in the surrounding environment that could be used as natural indicators, then practiced making acid-base indicators from these natural materials and uploaded them in video form to YouTube. Based on the results of the study, it was concluded that the CTL method with YouTube media can improve learning outcomes and creativity of Class XI MIPA 1 Even Semester SMA Negeri 1 Wedi in the 2021/2022 academic year, on acid-base indicator material. This can be seen from the increasing Daily Rating Results and videos uploaded on YouTube getting hundreds of viewers.